Pengaruh Media Audio terhadap Kemampuan Menyimak Bahasa Jerman Mahasiswa Program Studi Pendidikan Bahasa Jerman Universitas Negeri Makassar - Usman, Misnawaty; Asri, Wahyu Kurniati; Saleh, Nurming; Ernawati, Ernawati (Universitas Negeri Makassar, 2018)
This study aimed to obtain data about the influence on the ability listen to audio media students of German Language Study Program, Foreign Language Education Department Faculty of Languages and Literature, Makassar State University. The type of this research is a quantitative research using quasi-experimental. The research design used in this study is a pretest-posttest control group design. The population in this study is a student of German language Study Program, Foreign Language Education Department Faculty of Languages and Literature, Makassar State University 2016/2017, with the number of 46 people. The sample in this study is the total sample. Analysis of the data is an inferential statistical analysis using t-test. The calculation result is t test (8.61) > t table (2.015) with alpha level (0.05). That means, there is an effect using audio media on listening skills of students.